P278 First day fever: diagnosis? hyperimmunoglobulinemia d syndrome. (6th June 2017) - Yahşi, Aysun; Erat, Tuğba; Özdemir, Halil; Kara, Tuğçe Tural; Yalçınkaya, Fatoş; Ince, Erdal; Çiftçi, Ergin
Abstract : An 18-week-old girl, second child of non-consanguineous parents presented to our hospital due to nasal discharge, fever. On physical examination, her vital signs included a temperature of 39.2°C. Other findings were hyperemic oropharynx, right cervical 1*1 cm lymphadenopathy and macular rash with more markedly in the flexor surface of the forearm which has become prominent in the febrile period and than disappeared. A white whole blood count of 61.280/mm³(88% neutrophils, 9% lymphocytes, 2%monocyte) and ESR rate was 52 mm/h and CRP was 143.8 mg/L. Biochemical and urine analysis, .chest x-ray was normal. Medical history of the patient revealed that she had been admitted to neonatal service in an out centre upon fever developed at the postnatal 20th hour. Her physical examination was normal. White blood cell count of 23.160/mm³ and a CRP level of 31.6 mg/L. Patient who had normal chest x-ray and urinalysis had been put on iv vancomycin and meropenem. Cultures remained were negatif. Her fever had dropped at the 4th day and leukocytosis had regressed in the non-febrile period (14060/mm³). Patient whose fever had raised again to 39°C at the 8th day had a normal physical examination and developed leukocytosis (22.390/mm³), CRP (306 mg/L) Because the patient whose fever lasted 3 days had become febrile again at the 15th day of life, Cerebrospinal fluid was normal, ciprofloxacin iv had been added to the treatment and her fever had dropped after 3 days. The patient's discharged was planned at the 22nd day. Following non-febrile period of 40 days, patient had fever after vaccination when she was 60-day-old which had been attributed to vaccination since she had no any other symptom. In follow-up performed at the 75, 90, 106 and 120th days, patient had no any symptom except fevers lasting 3 day. The patient presented to our hospital when she was 130-day-old. Her family stated that, these rashes occurred during the last fever episodes and they attributed them to fever and in addition they reported that her vomiting was increasing in febrile periods. Upon fever episodes seen once in 15 days lasting 3 days accompanied by rash, vomiting, lymphadenopathy, elevated acute phase reactants and increased urinary mevalonic acid excretion, genetic analysis was ordered. Patient's MVK gene analysis I268T was found heterozygote and her diagnosis is hyperimmunoglobulinemia D syndrome.